The Impact of Current Ratio, Inventory Turnover, on Return on Assets In Listed Mining Sector Companies on IDX In 2019-2022 - Novi Dwi Putri; Miftah Alfarid Fathurahman; Astri Hartianti; Erwin Budianto (Publikasi Indonesia, 2024)
The mining sector in Indonesia is one of the fastest growing sectors and contributes significantly to the national economy. One of the important financial performance indicators for mining companies is Return On Assets (ROA). This study aims to analyze the effect of Current Ratio and Inventory Turnover on ROA in mining sector companies listed on the Indonesia Stock Exchange in 2019-2022. This research uses secondary data obtained from the financial statements of mining companies listed on the Indonesia Stock Exchange for 2019-2022. The data analysis technique used is multiple linear regression. The results showed that Current Ratio did not have a significant influence on ROA, while Inventory Turnover had a positive and significant influence on ROA. This means that the higher the Inventory Turnover, the higher the company's ROA. This study found that Inventory Turnover is a factor that affects ROA in mining sector companies listed on the Indonesia Stock Exchange in 2019-2022. Therefore, mining companies need to improve the efficiency of their inventory management to increase ROA.